On some measures to eliminate determinants that contribute to the commission of official crimes by employees of law enforcement agencies of Ukraine under martial law - Strelyuk, Ya. V. (Аналітично-порівняльне правознавство, 2025)
This scientific article analyzes law enforcement and judicial practice related to the prevention and counteraction to criminal offenses in the field of official activity committed by employees of law enforcement agencies of Ukraine, and based on the research results obtained in this regard, some measures have been developed aimed at eliminating, blocking, neutralizing, etc., the determinant complex of causes and conditions that contribute to the implementation of the specified illegal behavior by subjects of this type of crime. It is proven that in the system of criminologically significant measures in this regard, a priority place should be occupied by activities related to compliance and implementation by all law enforcement agencies of the constitutional and internationally recognized principle of the rule of law, which allows in this regard to prevent the commission of various offenses by officials and employees of the specified state authorities of Ukraine, as well as to eliminate the causes and conditions that contributed to their implementation in practice. It is stated that with the indicated criminological approach, an important role is played by such a legal institution of the civil legislation of Ukraine as the establishment of joint and several legal liability for subjects guilty of official crimes (in particular, by applying to them and their other accomplices the so-called «regression requirements»). Based on the analysis of current domestic legislation, relevant norms of international law and the practice of the European Court of Human Rights, it was concluded that only in cases of criminal offenses committed by law enforcement officers that do not relate to the scope of their official activities (for example, road accidents, crimes against property, economic offenses, etc.), the guilty persons who implemented their criminal intent in the form of intent or negligence are criminally liable either on general principles or with the application of the institution of joint and several liability, if the above-mentioned crimes were committed in complicity (Articles 26-28 of the Criminal Code (CC) of Ukraine).